Modern environmental state of soils of akdala massive (Journal of Geography and Environmental Management, 2018)
The article discusses the influence of presowing flooding of irrigated rice array on the seasonal dynamicsof soil processes. As well as the characteristic of negative processes and their consequences thatarise after the flooding of rice soils of the array, for example: lack of oxygen, harmful effects of hydrogensulfide in the rice culture.The paper describes the current ecological state takyr soils Akdalaarray degradation and waterloggingof soils. These processes are consequences of depressed economic conditions and the use of pesticidesand fertilizers in agriculture. In the last desyatiletiya in connection with the deterioration of reclamationcondition of irrigated soils in the arrays significantly decreased the fertility continues dehumification andecological condition of soils. In some regions of Kazakhstan, much of the land unusable due to salinity.Of the above environmental issues affect the reduction of humus, nutrients, physico-chemical andbiological properties of soil, which in turn affects productivity and quality of rice. This article describesthe environmental problems of Kazakhstan soils associated with zatuplenie array. The study of the influenceof presowing flooding of irrigated rice array on the seasonal dynamics of soil processes is veryimportant for our country.The analysis of literary sources shows that in the rice areas of the Republic has developed an environmentallyunfavorable situation. This reduces the potential for socio-economic development of theRepublic, particularly, the resource base of the rural economy. In this regard, of particular urgency isthe creation of a scientific and theoretical foundations of the holistic concept of fertility reproduction ofperiodically flooded soils.